1990
DOI: 10.3181/00379727-195-43142
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Pyridoxine-5'- -d-Glucoside by a Broad-Specificity  -Glucosidase from Mammalian Tissues

Abstract: Research was conducted to evaluate the ability of a broad-specificity beta-glucosidase in mammalian tissues to catalyze the hydrolytic release of free pyridoxine from pyridoxine-5'-beta-D-glucoside, a naturally occurring form of vitamin B6 in plant-derived foods. Activity was detected in liver and intestinal mucosa using tritiated pyridoxine glucoside as a substrate. In the rat and guinea pig, enzyme activity was greater in intestine than in liver or kidney while even greater activity was detected in human int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…The specific activity of pyridoxine-␤-D-glucoside hydrolase in human jejunum is approximately 5.8-fold greater than that of rat intestine (12). This difference is consistent with the greater in vivo bioavailability of orally administered PNG in humans than rats.…”
Section: Figsupporting
confidence: 69%
See 2 more Smart Citations
“…The specific activity of pyridoxine-␤-D-glucoside hydrolase in human jejunum is approximately 5.8-fold greater than that of rat intestine (12). This difference is consistent with the greater in vivo bioavailability of orally administered PNG in humans than rats.…”
Section: Figsupporting
confidence: 69%
“…We have shown in the present study that pyridoxine 5Ј-␤-D-glucoside is hydrolyzed by a specific enzyme present in pig intestinal mucosal cytosol but not by the cytosolic broad specificity ␤-glucosidase. We have also shown that pyridoxine-␤-D-glucoside hydrolase activity exists in rat, guinea pig, and human intestinal mucosal cytosolic fractions (12,54). As shown in the present study, our previous assumption that the intestinal cytosolic broad specificity ␤-glucosidase was solely responsible for hydrolysis of PNG in rat, guinea pig, and human intestine (12) is incorrect.…”
Section: Figcontrasting
confidence: 48%
See 1 more Smart Citation
“…Although the intestinal B-glucosidase responsible for in vivo hydrolysis of PN-5'-B-D-glucoside has not been isolated and characterized, this enzyme has been shown to be highly similar to the cytosolic broad specificity B-glucosidase in other mammalian tissues (50). The intestinal B-glucosidase activity capable of hydrolyzing PN-5'-B-D-glucoside was mainly cytosolic, optimally active at pH 6, and was inhibited by sodium taurocholate.…”
Section: Nutritional Properties Of Vitamin B6-b-glucosidesmentioning
confidence: 98%
“…cytosolic) hydrolysis of PNG in mammalian small intestinal mucosa. Intestinal cytosolic PNG hydrolysis was initially thought to be catalyzed by a broad specificity ␤-glucosidase (BS␤G) (EC 3.2.1.21) (11), a cytosolic enzyme found in the intestine and liver (12)(13)(14). Cytosolic PNG hydrolysis was also reported to be inversely related to vitamin B 6 nutritional status in rodents (13,14).…”
mentioning
confidence: 99%